Enhanced thermal and mechanical properties of poly(trimethylene terephthalate-block-poly(tetramethylene oxide) segmented copolymer based hybrid nanocomposites prepared by in situ polymerization via synergy effect between SWCNTs and graphene nanoplatelets - S. Paszkiewicz; A. Szymczyk; K. Livanov; H. D. Wagner; Z. Roslaniec (eXPRESS Polymer Letters, 2015)
Graphene nanoplatelets/single walled carbon nanotubes/poly(trimethylene terephthalate-block-poly(tetramethylene oxide) segmented copolymer (GNP/SWCNT/PTT-PTMO) hybrid nanocomposites were synthesized via in situ polymerization. A remarkable synergistic effect between GNPs and SWCNTs on improving thermal and mechanical properties of nanocomposites based on segmented block copolymers was observed. Heterogeneous structure of the PTT-PTMO allowed for a better and more uniform distribution of both types of nanoparticles and stabilized the structure in question. This enabled us to observe a so-called ‘synergistic effect’, caused by the use of mixture of carbon nanotubes and graphene nanopletelets, on the enhancement of thermal and mechanical properties of the obtained polymer. In order to ascertain the influence of mentioned carbon nanostructures on the nano-phase-separated structure of the synthesized PTT-PTMO block copolymers, differential scanning calorimetric (DSC) and dynamic mechanical thermoanalysis (DMTA) measurements were performed. Scanning electron microscopic (SEM) and transmission electron microscopic (TEM) images of the PTTPTMO nanocomposites displayed that hybrid nanofillers exhibited better distribution and compatibility than SWCNTs and GNPs did individually. The tensile modulus of 0.5SWCNT/0.1GNP/PTT-PTMO composites was 68% higher than that of the PTT-PTMO alone, compared to only a 10 and 28% increase in tensile modulus for 0.3GNP/PTT-PTMO and 0.3SWCNT/PTT-PTMO composites respectively (the highest concentration when single nanofiller was added).